PEMIMPIN PEREMPUAN DALAM FILM RAYA AND THE LAST DRAGON - Frizie Febriani Sihole; Ade Kusuma (Jurnal Komunikasi Universitas Garut: Hasil Pemikiran dan Penelitian, 2022)
Abstract Disney animated films are in great demand by audiences of all ages. The presence of various Disney princess characters attracts the audience's attention, thus becoming a role model for most girls who like Disney Princess. The development of the main female character in Disney animated films has experienced a significant shift. From 1937 until now, there have been three divisions of the Disney princess era, including The Classic Princesses, Rebels Era, and Contemporaries Era. Film Raya and The Last Dragon is a Disney animated film released in 2021. The main female character in the film is a warrior from the land of Kumandra. This study explores how women leader are depicted in Raya and The Last Dragon. This study was analyzed by the Barthes semiotics method in the form of two stages of significance, denotation, and connotation. This research will see how the narrative and cinematic elements in the film make it easier for researchers to answer the formulation of the problem. This study explains that there is a shift in the character of the main character, namely Raya, who is represented as a women leader. Female characters in Disney films and the development of femininity also began to be adjusted. The myth that circulated about women's weak ability to lead was successfully broken in the film Raya and The Last Dragon. In the analysis that has been carried out, the findings obtained are that female leaders through Raya figures are constructed as figures who are willing to sacrifice, brave, strong, and independent. Keywords: Disney; animated film; women leader; semiotics. AbstrakFilm animasi produksi Disney banyak diminati penonton dari beragam usia. Kehadiran ragam tokoh Disney princess mampu menarik perhatian penonton, hingga menjadi role model bagi sebagian besar anak-anak perempuan yang menyukai Disney Princess. Perkembangan karakter tokoh utama perempuan dalam film animasi Disney mengalami pergeseran yang cukup berarti. Sejak tahun 1937 hingga sekarang sudah terdapat tiga pembagian era Disney princess, diantaranya The Classic Princesses, Rebels Era dan Contemporaries Era. Film Raya and The Last Dragon merupakan film animasi Disney yang dirilis tahun 2021. Tokoh utama perempuan dalam film tersebut adalah seorang pendekar yang berasal dari negeri Kumandra. Penelitian ini bertujuan untuk mengeksplorasi tentang pemimpin perempuan digambarkan dalam film Raya and The Last Dragon. Penelitian ini dianalisis menggunakan metode semiotika Barthes berupa signifikasi dua tahap, denotasi dan konotasi yang kemudian dibagi dalam penanda, petanda, level denotasi dan konotasi. Penelitian ini akan melihat bagaimana unsur naratif dan sinematik dalam film tersebut, untuk mempermudah peneliti menjawab rumusan masalah. Hasil penelitian ini menjelaskan adanya pergeseran karakter tokoh utama yaitu Raya yang direpresentasikan sebagai pemimpin perempuan. Tokoh perempuan dalam film Disney seiring dengan perkembangan feminitas juga mulai disesuaikan. Mitos yang beredar tentang kemampuan lemah perempuan dalam memimpin berhasil dipatahkan pada film Raya and The Last Dragon. Berdasarkan analisis yang telah dilakukan, peneliti menemukan bahwa pemimpin perempuan melalui tokoh Raya dikonstruksi sebagai sosok yang rela berkorban, berani, kuat dan mandiri.Kata-kata kunci: Disney; Film Animasi; Pemimpin Perempuan; Semiotika.